Management Femoral Fracture in Cats using Intramedullary Pin and Wires Fixation - Erwin Erwin; Deni Noviana; Dany Umbu; Tri Isyani Tungga Dewi (The Faculty of Veterinary Medicine of Syiah Kuala University, 2018)
On April 2016, Veterinary Teaching Hospital, Faculty of Veterinary Medicine, Bogor Agricultural University (VTH FKH IPB) received 4 cases of femoral fractures in cats caused by trauma. Two cats suffered oblique diaphysis fracture femoral, one cat suffered comminuted diaphysis fracture femoral, and one cat suffered epiphyseal fracture femoral (column femoral and trochanter major). All cats were treated by open surgery using intramedullary pins (Steinmann) and cerclage wires (Kirschner). Fracture recovery went without complication and all cats were able to move their feet one week after surgery.